Free Education For The Girl Child In Public Secondary Schools In Nigeria: It’s Impact On Enrolment - Brambaifa, Anna Preye (Archives of Business Research, 2019)
All over the world, education has been recognized as an effective tool for societal development. Educating the girl-child has however faced impediments as a result of societal prejudice which has immensely affected the enrollment of girls in secondary schools. In recognition of this impediment, numerous governments have put in place measures such as “free education for all” to encourage gender balance in the educational system. This study is therefore informed by the need to analyse the impact of free education for the girl child and its impact on enrolment in secondary schools. The research established that free education for all in the long term favors the male child because of socio-economic and religious impediments affecting the girl. The sustainability of these measures has over the years being affected by poor implementation, financing and accountability. Thus, employing a stratified ransom random sampling technique and structuring a 4 pointer likert scale questionnaire titled “Free Education and Enrolment for the Girl-Child in Public Secondary School Questionnaire” (FEEGPQ) which used to obtain responses from the participants. A correlation coefficient of 0.89 was obtained using the split-half reliability method. The data was analyzed using the (statistical package for social science) SPSS version 22 and the results indicated that free education targeted at girls will greatly impact the enrolment of girls while identifying that location plays no role in how free education is perceived by the public.